Quaderni del LUDiCa - Salice, Giampaolo; Schivo, Beatrice (Quaderni del LUDiCa, 2022)
This first issue of the "Quaderni del LUDiCa" series recounts the first edition of LUDiCa, the University of Cagliari's digital humanities lab. A narrative developed by the students who were protagonists both of the first phase of the lab (Bottega Digitale), in which they experienced for the first time the intersection between digital tools and humanities studies, and of the Digital and Public History Summer Camp, held in the Municipality of Nuraminis, in collaboration with the local municipal administration, associations and citizens.